Platos Phaedrus: dialectic as the method of philosophical inquiry - Madriñan Molina, Adriana (2017)
Plato thought that dialectic is the method of philosophical inquiry. Yet there is no agreement between scholars regarding Plato\'s view of dialectic. The dominant interpretation, dating back to Robinson\'s Plato\'s Earlier Dialectic, which I call the \"discontinuous\" interpretation (DI), assumes a significant gap between Plato\'s account of dialectic as it is presented in the course of the dialogues. As such, although Plato considered dialectic as the method of philosophical inquiry, the term \'Dialectic\' is just a façon de parler conveying the method he deemed most suitable at different moments. One should note that (DI) entails the following trilemma: Plato\'s dialectic, as the method of philosophical inquiry, must be identified with either Elenchus (E), Hypothesis (H) or Collection & Division (C&D). For example, Irwin (1988:7) argues that one should identify dialectic with (E) while Benson (2015:238) argues that one should identify dialectic with (H). In contrast with (DI), the goal of this dissertation is to defend a \"continuous\" interpretation (CI): Plato introduced a unified view of dialectic as the method of philosophical inquiry in the Phaedrus. My argument supporting (CI) relies on three main premises: (1) The so-called three methods, (E), (H) and (C&D), are three different procedures of one διαλεκτικὴ τέχνη; (2) Plato\'s διαλεκτικὴ τέχνη is both a method of communication and a method of discovering truth; and (3) The Phaedrus (261a-266b) contains Plato\'s unified view of διαλεκτικὴ τέχνη, conceived as an amalgam of (E), (H) and (C&D), and a method of communication and a method of discovering truth.